Improvement in the survival of patients with stage IV non-small-cell lung cancer: Experience in a single institutional 1995–2017. (May 2019) - Takano, Natsuki; Ariyasu, Ryo; Koyama, Junji; Sonoda, Tomoaki; Saiki, Masafumi; Kawashima, Yosuke; Oguri, Tomoyo; Hisakane, Kakeru; Uchibori, Ken; Nishikawa, Shingo; Kitazono, Satoru; Yanagitani, Noriko; et al.
Highlights: The survival of advanced non-small-cell lung cancer improved in last two decades. The approval of new classes of drugs impacted on the survival improvement. The approval of similar types of drug may not impact on the survival benefit. Abstract: Objectives: In the past two decades several antineoplastic agents have been approved for the treatment of advanced non-small-cell lung cancer (NSCLC), and the management of these patients has drastically changed. However, there is limited information regarding the impact of these advances on patient survival in clinical practice. Materials and methods: We analyzed the survival of patients with stage IV NSCLC who received any treatment in the Cancer Institute Hospital of the Japanese Foundation for Cancer Research (JFCR) between January 1, 1995 and March 1, 2017. A total of 1, 547 consecutive patients were included in this case series. In this analysis, five diagnostic periods were evaluated: 1995–1999 (period A), 2000–2004 (period B), 2005–2009 (period C), 2010–2014 (period D), and 2015–2017 (period E). We compared overall survival (OS) between the periods before and after propensity score matching (PSM) and in patients with EGFR mutation, with ALK fusion gene, or without driver mutation. Results: In the past two decades the OS of patients with stage IV NSCLC improved. The median OSs for periods A, B, C, D, and E were 9.0, 11.0, 13.7, 17.9 months, and not reached, respectively. After PSM with known baseline characteristics, the trend of improvement in OS was similar. However, the OS of patients with EGFR mutation or ALK fusion gene did not improve between periods, despite the availability of several tyrosine kinase inhibitors in Japan. The OS of patients without a driver mutation was slightly longer in the period E. Conclusion: The introduction of new classes of drugs has significantly improved the survival of patients with stage IV NSCLC. However, the approval of similar types of drugs may not be associated with further improvement in survival.